Implementation of the Sensory Play Method to Develop Children's Fine Motor Skills at PAUD Bina Insania Arrahman, Ternate City - Adiyana Adam; Ariyanti Ade; Aprilia Higoro; Puji Dwi Rahayu (Manunggal Halim Jaya, 2026)
This study aimed to describe the implementation of sensory play methods in developing children's fine motor skills at PAUD Bina Insania Arrahman, Ternate City. The study used a descriptive qualitative approach with 15 group B children as subjects and two class teachers and one principal as informants. Data collection techniques included participatory observation, in-depth interviews, documentation, and field notes. Data analysis used the interactive model of Miles, Huberman, and Saldaña, with triangulation for data validity. The results of the study showed: (1) planning was carried out systematically through RPPH integrated with the learning theme, carried out at least three times a week for 30-45 minutes; (2) implementation used varied materials including playdough, water, sand, seeds, and local natural materials with teachers acting as facilitators, observers, motivators, guides, and models; (3) children's fine motor development increased significantly with tripod grasp abilities increasing to 80%, eye-hand coordination 87%, pincer grasp 87%, and bilateral coordination 73%; and (4) obstacles including limited space and preparation time were overcome through the use of outdoor activities, parental cooperation, and intensive communication. Conclusion: The implementation of the sensory play method effectively develops children's fine motor skills through the creative use of local materials and child-centered learning.